2022
DOI: 10.3390/microorganisms10020384
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae Strains Modulate Human Dendritic Cell Functions and Affect TH1/TH17 Response

Abstract: Hypervirulent Klebsiella pneumoniae (Hv-Kp) strains have emerged as pathogens causing life-threatening, invasive disease even in immunocompetent hosts. Systemic dissemination usually occurs following perturbations of the gut microbiota and is facilitated by Hv-Kp resistance to phagocytosis and complement activity. Hv-Kp are usually associated with K1 or K2 capsular types, produce several iron uptake systems (e.g., aerobactin and salmochelin) and are often but not invariably, capsular material hyper-producers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The iucABCD gene cluster encodes the aerobactin synthase, and the membrane protein receptor is encoded by the iutA gene. The iroA ( iroBCDN gene cluster) encodes salmochelin ( Paczosa and Mecsas, 2016 ; Palmer and Skaar, 2016 ; Nicolò et al, 2022 ), allowing bacteria to uptake sufficient iron for growth and reproduction. The results of this study showed that the positive rates of the rmpA , peg-344 , and iroB genes in CSKP were 44.1, 42.7, and 45.5%, respectively, significantly higher than in CRKP, while there were no significant differences in the positive rates of the rmpA2 and iucA genes.…”
Section: Discussionmentioning
confidence: 99%
“…The iucABCD gene cluster encodes the aerobactin synthase, and the membrane protein receptor is encoded by the iutA gene. The iroA ( iroBCDN gene cluster) encodes salmochelin ( Paczosa and Mecsas, 2016 ; Palmer and Skaar, 2016 ; Nicolò et al, 2022 ), allowing bacteria to uptake sufficient iron for growth and reproduction. The results of this study showed that the positive rates of the rmpA , peg-344 , and iroB genes in CSKP were 44.1, 42.7, and 45.5%, respectively, significantly higher than in CRKP, while there were no significant differences in the positive rates of the rmpA2 and iucA genes.…”
Section: Discussionmentioning
confidence: 99%
“…There was a report that hvKp strains with thick polysaccharide capsules are able to resist neutrophil phagocytosis and complement-mediated killing ( Nicolò et al., 2022 ). Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to classical K. pneumoniae (cKp), this strain, especially K1 and K2 serotypes, can cause more severe and metastatic infections such as pyogenic liver abscesses, endophthalmitis, and meningitis even in immunocompetent hosts of any age ( Russo and Marr, 2019 ). The presence of genotypic markers iucA, peg-344, and rmpA can be used, albeit imperfectly, to most accurately distinguish the cKp and hvKp strains as previously reported ( Nicolò et al., 2022 ). There was a high prevalence of hvKp among K. pneumoniae isolates ranging from 31% to 37.8% in China ( Zhang et al., 2016 ).…”
Section: Introductionmentioning
confidence: 96%
“…The external cell signaling regulatory kinase, IL-6, and STAT3 pathways jointly drive IL-17 expression ( 63 ). Another study found that mice lacking IL-17A receptors reduced Th1 immune-dependent infections, such as tuberculosis, but were unable to fight pulmonary Klebsiella pneumoniae infection because these mice had a reduced ability to recruit granulocytes to clear the infection ( 64 , 65 ). The production of IL-17 was also required.…”
Section: Role Of Th17 Cells In Mucosal Immunitymentioning
confidence: 99%